Analisis Pengelolaan Dan Realiasi Anggaran Dana Bantuan Operasional Sekolah (BOS) Pada SMPK Pancasila Lekebai - Gabriela Florensia Bura; Maria Nona Dince; Yoseph Darius Purnama Rangga (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine and analyze the management and realization of the Shcool Operational Assistance (BOS) fund budget at SMPK Pancasila Lekebai. This study uses a type of qualitative research, where the data is obtained from direct observations to several informants interviewed and then analyzed the data acquisition and then drawn conclusions from the result of the interview, as well as other supporting documents related to the management and realization of the BOS fund budget. Data collection techniques are used through interview observation and documentation. Data analysis techniues are used through several stages, namely data collection, data reduction, data presentation, and conclusion withdrawal/verification. The results showed that the management and realization of the BOS fund budget at SMPK Pancasila Lekebai was in accordance with Juknis. Starting with the preparation of RKAS, the implementation of use in accourdance with the components listed in the Juknis and shcool needs, until an accountability report is made. However, there is an obstacle that occurs in the lack of shcool committee supervision on reporting the use of BOS funds which is considered normal.